Study of Agricultural Land Conversion on the Availability of Ocean Water in Maintaining Terrestial Ecosystems - Dewi Fortuna Khairil; Abdul Razak (Postgraduate School, Universitas Negeri Padang, 2023)
Land is a natural resource that has an important role in the development of a country. The purpose of this research is to find out how the study of agricultural land conversion and its relation to water availability in maintaining the land ecosystem. The method used in this research is a literature review or literature review of several previous studies. One of the problems faced in land development is the lack of water catchment areas due to land conversion. The lack of water availability triggered by the conversion of agricultural land areas certainly has a very diverse impact, such as a lack of food supply, and a decrease in soil quality. so it can be concluded that the conversion of agricultural land and the availability of water in maintaining terrestrial ecosystems are closely related.